De la psicología a la autonomía del mundo 3. Acercamiento a la controversia de los factores psicológicos entre Popper y Kuhn - Arcia Grajales, John Harvy (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The present paper intends to show how controversy on psychological factors between Karl Popper and Thomas Kuhn goes through a provoked interpretation that Kuhn makes without knowing that the proposal in words 1, 2 and 3 never goes from a physical state to a scientific state thanks to overcoming and excision. Each world however, moves among ascending levels of complexity which go beyond fundamental conditions from which they (the worlds) emerge, but, at the same time, these worlds are cradled by those conditions. It is for this reason that is said that myths and psychological factors never abandon the scientific discourse. This, since critical reason needs them at the time of discussing the ethical-political responsibility when making proposals for humankind.